2020
DOI: 10.3390/cancers12082248
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Balance between ZEB Family Members Is Important for Melanocyte Homeostasis and Melanoma Progression

Abstract: It has become clear that cellular plasticity is a main driver of cancer therapy resistance. Consequently, there is a need to mechanistically identify the factors driving this process. The transcription factors of the zinc-finger E-box-binding homeobox family, consisting of ZEB1 and ZEB2, are notorious for their roles in epithelial-to-mesenchymal transition (EMT). However, in melanoma, an intrinsic balance between ZEB1 and ZEB2 seems to determine the cellular state by modulating the expression of the master reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 129 publications
1
25
0
Order By: Relevance
“…Nucleosome remodeling and deacetylation (NuRD) complexes contains HDAC1/2 and chromodomain helicase DNA-binding proteins [ 185 ]. The NuRD complex binds to both ZEB1 and ZEB2 [ 186 ]. This complex binds to the NuRD-interacting motif that is close to the N-terminal of ZEB2 [ 186 ].…”
Section: Regulation Of the Zeb Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleosome remodeling and deacetylation (NuRD) complexes contains HDAC1/2 and chromodomain helicase DNA-binding proteins [ 185 ]. The NuRD complex binds to both ZEB1 and ZEB2 [ 186 ]. This complex binds to the NuRD-interacting motif that is close to the N-terminal of ZEB2 [ 186 ].…”
Section: Regulation Of the Zeb Familymentioning
confidence: 99%
“…The NuRD complex binds to both ZEB1 and ZEB2 [ 186 ]. This complex binds to the NuRD-interacting motif that is close to the N-terminal of ZEB2 [ 186 ]. The domains of ZEB1 that interact with the NuRD complex are not known [ 187 ].…”
Section: Regulation Of the Zeb Familymentioning
confidence: 99%
“…Multiple extracellular factors have been identified that induce the phenotypic switch toward an invasive phenotype, including hypoxia, low nutrient (low glucose and amino acid limitation), and inflammatory signaling, including TGFβ and tumor necrosis factor α (TNFα), etc., in addition to cell intrinsic factors (e.g. oncogenic drivers) 13,84 . Also, it is becoming evident that epigenetic modifications to suppress the expression of MITF and its targets and therapeutic interventions (i.e.…”
Section: Phenotypic States Based On Gene Expression Profilesmentioning
confidence: 99%
“…Another important family of transcription factors, the zinc-finger E-box-binding homeobox family of transcription factors (ZEBs) ZEB1 and ZEB2 are known for their ability to induce EMT-driven cellular plasticity in carcinoma progression [163,164]. However, in melanoma, ZEB1 and ZEB2 function antagonistically and play a central role in "phenotype switching" by modulating the expression of microphthalmia-associated transcription factor (MITF), a master regulator of melanocyte homeostasis and differentiation.…”
Section: Mechanisms Regulating Lineage Plasticitymentioning
confidence: 99%
“…However, in melanoma, ZEB1 and ZEB2 function antagonistically and play a central role in "phenotype switching" by modulating the expression of microphthalmia-associated transcription factor (MITF), a master regulator of melanocyte homeostasis and differentiation. Increased ZEB2 expression drives the expression of MITF leading to a differentiated and proliferative cell state whereas increased ZEB1 expression lowers MITF and leads to a stem-like and invasive cell state [163,[165][166][167].…”
Section: Mechanisms Regulating Lineage Plasticitymentioning
confidence: 99%